A new approach to dreams in psychotherapy: Phenomenological dream-self model - (:unkn) unknown (Kure Iletisim Grubu A.S., 2019)
Whether it is in traditional or modern context, dreams have a special place in both psychology and psychotherapy studies. 'The Traditional Interpretive Dream Approach' model, which we had come across its first remains in Mesopotamia and is also the inspiration for psychoanalysis, is based on the interpretation of the symbols in the dream with the principle of reaching the hidden meaning. However, what is done with this interpretation is to move away frodm the phenomenal subjective reality of the client. Our psychotherapy practice has forced us to see this fact in time: Dreams are also experiences just like the waking experiences and a phenomenal self has its place in the center of these experiences as it has in the waking ones. We modeled the dream studies in which we take dream self in the center and we called this model as 'Phenomenological Dream Self Model '(PDSM). The PDSM proposes a self-centered view and takes its theoretical background from its deepened practice. This practice also brings PDSM closer to the phenomenological view, in principle not based on the unconsciousness but on the consciousness of the dream self. There are four stages of PDSM. In the first stage the dream self-experience and in the second stage the waking self- experience are examined. These two are compared in the third stage and in the fourth stage, the associations related to dream are examined on the basis of the phenomenology of the dream self. © 2019 Kure Iletisim Grubu A.S.. All rights reserved.
Keywords: Dream works; Phenomenological dream self-model; Psychotherapy; Self